Serum Lactate –An indicator of morbidity and mortality in polytrauma and multi-trauma patients - Lamichhane, P; Shrestha, S; Banskota, B; Banskota, AK (Nepal Orthopaedic Association Journal, 2013)
Background: The search for the best marker or set of markers for the diagnosis, prognosis and treatment of ‘at risk’ trauma patients is ongoing. Serial estimation of serum lactate values are thought to help predict morbidity and mortality in trauma victims. There is evidence to support the use of blood lactate levels as an end point of resuscitation. The presence of elevated lactic acid levels in the serum can direct the treating physician to safe and correct timing of any surgical intervention. Early identification and aggressive resuscitation measures aimed at correcting the impaired metabolic dysfunction improves survival and reduces complications in severely injured trauma patients. Methods: A prospective analytical study of 52 patients with polytrauma and multiple trauma admitted within 12 hours of injury to our institution between March 2007 to February 2008 was carried out. All the patients were resuscitated as per the advance trauma life support (ATLS) protocol in the emergency room. Serum lactate level was analyzed on the 1st, 5th and 14th day of injury. Serum lactate levels greater than 2 milimoles/L was considered abnormal and serum lactate level greater than 5 milimoles/L was considered significant. Results: There were 45 males and 7 females with an average age of 32.8 years (18-82). 18 patients out of 52 sustained polytrauma. Of these 18 patients, 8 patients sustained chest injury, 4 had head injury and 2 had abdominal injury. In the polytrauma group (n-18), 5 patients had an elevated lactate above 2 milimoles/Lon admission. 2 patients who had significant rise of lactate (>5 milimoles/L) on admission died on the 5th day. Out of 34 multiple trauma patients, 13 patients had an elevated lactate level at admission. One patient in this group with lactate level 7.2 died of ARDS on 3rd day of admission. Conclusion: Blood lactate appears to be a reliable marker reflecting not only the severity of the shock, but also for predicting survival. The longer the lactate is elevated, the more a patient is likely to develop multiple organ dysfunctions and die. Lactate levels followed over time is more reliable than isolated values. DOI: http://dx.doi.org/10.3126/noaj.v2i1.8134 Nepal Orthopaedic Association Journal Vol.2(1) 2011: 7-13